Club Méditerranée: One of the most optimal formulas of club vacation in sport and recreation tourism - Pavlović Tamara (Zbornik Radova: Geografski institut "Jovan Cvijić", 2007)
Club Méditerranée is a tourist corporation of hybrid character, functioning both as a tour operator and as a specific hotel chain. By providing additional services, i.e. tourist animation, sports and cultural activities, it offers one of the most optimal "all inclusive" tourist products on the world market. The Club invests a lot of effort and resources in the redesign and enhancement of its products and services in order to be able to meet the constantly evolving demand of its clients. The range of offered services meets the highest standards of quality enabling the Club to act as the leader in the organisation of highly prestigious holidays. Its success largely depends on the professionalism and constant availability of its staff, who contribute to the creation of a welcoming and friendly atmosphere, ensuring a sense of happiness and satisfaction for its clients. The Club is the most renowned for its versatile offer of sport activities. One of its leading goals is to further enhance the sport experience of its clients. The sport offer of the Club comprises of around 60 different physical activities, including sailing, billiard, horseback-riding, basketball, soccer, kayaking, volleyball, surfing, water-skiing, table tennis, archery, roller-skating and similar. The provision of different courses and trainings in tennis, golf, scuba diving, skiing, snowboarding and similar are a great attraction for numerous tourists. Apart from the organization of typical sport activities, the Club also has on its offer a wide range of fitness classes, therapies, massage and body treatments, therefore it can also be considered as a fitness clinic. Each resort run by the Club provides these services using floral extracts and aromatherapies according to the latest fashion. All treatments are aimed at reducing the level of stress and relaxing both the body and the mind of the clients, with the aim to provide a sensation of a 'total man'.